Adhesive composition for peeling off by irradiation with light, laminate, and method for producing laminate and peeling method

JP7633592B2Active Publication Date: 2025-02-20NISSAN CHEM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020558377
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-27
Filing Date
2019-11-18
Publication Date
2025-02-20
Estimated Expiration
2039-11-18

AI Technical Summary

Benefits of technology

【0014】 本発明で用いる所定の光吸収性有機化合物、特に比較的安価であるという利点と有機溶媒への高溶解性を示すという利点を有するチオインジゴ誘導体やイソチオインジゴ誘導体は、良好な光吸収能を有することから、これを接着剤成分と混合することにより、ウエハー等の被加工体の加工がされている時は支持体と被加工体との間で好適に接着し、且つ、加工の後は、レーザーを好適に吸収し接着強度が低下して剥離できる、光照射剥離用接着層として好適な薄膜を与える組成物を容易に調製できる。それ故、本発明の光照射剥離用接着剤組成物を用いることで、支持体やウエハー等の被加工体に剥離のための過度な荷重をかけずにレーザーで剥離可能な接着層を製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633592000001
    Figure 0007633592000001
  • Figure 0007633592000002
    Figure 0007633592000002
  • Figure 0007633592000003
    Figure 0007633592000003
Patent Text Reader

Abstract

A light-irradiation peelable adhesive composition that can be peeled off by irradiation with light, comprising an adhesive component (S) and a light-absorbing organic compound (X), wherein the light-absorbing organic compound (X) contains, in its molecule, one or more aromatic rings, one or more rings containing heteroatoms as ring-constituting atoms, and one or more groups selected from a carbonyl group and a thiocarbonyl group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition for peeling off by light irradiation, a laminate, and a method for producing and peeling off the laminate. [Background technology]

[0002] Conventionally, semiconductor wafers have been integrated in a two-dimensional plane, but for the purpose of further integration, there is a demand for semiconductor integration technology that integrates (stacking) the plane in a three-dimensional direction. This three-dimensional stacking is a technology that integrates multiple layers while connecting them with through silicon vias (TSVs). When integrating multiple layers, each wafer to be integrated is thinned by polishing the side opposite the circuit surface (i.e., the back side), and the thinned semiconductor wafers are stacked.

[0003] Semiconductor wafers before thinning (also simply called wafers here) are bonded to a support in order to be polished by a polishing device. The bond at this time must be easily peeled off after polishing, and is therefore called temporary bonding. This temporary bonding must be easily removed from the support, and if a large force is applied to remove it, the thinned semiconductor wafer may be cut or deformed, so it is easily removed to prevent such things from happening. However, it is undesirable for the semiconductor wafer to come loose or shift due to the polishing stress when the back surface of the semiconductor wafer is polished. Therefore, the performance required of the temporary bonding is to withstand the stress during polishing and to be easily removed after polishing.

[0004] For example, the material is required to have high stress (strong adhesive strength) in the planar direction during polishing, and low stress (weak adhesive strength) in the vertical direction during removal.

[0005] A method using laser irradiation has been disclosed for such bonding and separation processes (see Patent Documents 1 and 2).

[0006] However, the temporary adhesives used in these bonding and separation processes generate heat when irradiated with a laser, which is thought to pose a risk of causing significant damage to the wafer. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2004-64040 A [Patent Document 2] JP 2012-106486 A Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesive composition for peeling by light irradiation which provides a thin film suitable as an adhesive layer that has excellent heat resistance when bonding (curing) a support, when processing the back surface of a wafer, and even during the component mounting process, and which can be easily peeled off by irradiating a laser when peeling off the support; and a laminate using the same, as well as a method for producing the laminate and a method for peeling it off. [Means for solving the problem]

[0009] As a result of extensive research to solve the above problems, the inventors have found that a film obtained from a composition containing an adhesive component and a specified light-absorbing organic compound is suitable as an adhesive layer that has excellent heat resistance when joining (curing) the support, when processing the back surface of the wafer, and even during the component mounting process, and that can be easily peeled off by irradiating with a laser when peeling off the support, and have completed the present invention.

[0010] That is, the present invention provides 1. A photoirradiation peelable adhesive composition that can be peeled off by irradiation with light, Contains an adhesive component (S) and a light absorbing organic compound (X), a light-irradiation peelable adhesive composition, characterized in that the light-absorbing organic compound (X) contains, in its molecule, one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more groups selected from a carbonyl group and a thiocarbonyl group; 2. A photoirradiation peelable adhesive composition that can be peeled off by irradiation with light, Contains an adhesive component (S) and a light absorbing organic compound (X), the light-absorbing organic compound (X) contains, in its molecule, one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more carbonyl or thiocarbonyl groups; 3. The adhesive composition for peeling off upon light irradiation according to 1 or 2, wherein the light-absorbing organic compound (X) contains, in its molecule, two or more aromatic rings, two or more rings containing heteroatoms as ring-constituting atoms, and two or more carbonyl groups or thiocarbonyl groups. 4. The adhesive composition for peeling off by light irradiation according to 3, wherein the aromatic ring is condensed with a ring containing the heteroatom as a ring-constituting atom, and the carbon atom of the carbonyl group or the thiocarbonyl group is a ring-constituting atom of the ring containing the heteroatom as a ring-constituting atom. 5. An adhesive composition for peeling off upon light irradiation 1 or 2, wherein the light-absorbing organic compound (X) is represented by formula (T1-1) or (T2-1):

[0011] [ka] (X 1 ~X 4 are carbon atoms constituting an aromatic ring, and are each independently bonded to a hydrogen atom, a halogen atom, or a monovalent organic group other than the carbon atom constituting the aromatic ring; X 5 represent, independently of each other, a heteroatom. 6. The light-irradiation peelable adhesive composition according to 1 or 2, wherein the light-absorbing organic compound (X) is a thioindigo derivative or an isothioindigo derivative. 7. The light irradiation peelable adhesive composition according to claim 6, wherein the thioindigo derivative or isothioindigo derivative is represented by formula (T1-2) or (T2-2).

[0012] [ka] (In the formula, each R A are atoms or groups substituted on the benzene ring, each independently representing a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or an aryl group, and a to d are each independently an integer of 0 to 4. 8. The light irradiation peelable adhesive composition according to claim 7, wherein the thioindigo derivative or isothioindigo derivative is represented by formula (T1-3) or (T2-3).

[0013] [ka] (In the formula, each R B and each R C each independently represents a hydrogen atom, a halogen atom, or an alkyl group. 9. The photoirradiation peelable adhesive composition according to any one of 1 to 8, wherein the adhesive component (S) contains a component (A) that cures by a hydrosilylation reaction. 10. Any of the light irradiation peelable adhesive compositions of 1 to 9, further comprising a component (B) containing at least one selected from the group consisting of a component containing an epoxy-modified polyorganosiloxane, a component containing a methyl group-containing polyorganosiloxane, and a component containing a phenyl group-containing polyorganosiloxane; 11. The component (A) that cures by a hydrosilylation reaction is a siloxane unit (Q unit) represented by SiO2, R 1 R 2 R 3 SiO 1 / 2 Siloxane unit (M unit) represented by R 4 R 5 SiO 2 / 2 Siloxane units (D units) represented by the formula 6 SiO 3 / 2 Polysiloxane (A1) containing one or more units selected from the group consisting of siloxane units (T units) represented by the above R 1 ~R 6are a group or atom bonded to a silicon atom, and each independently represent an alkyl group, an alkenyl group, or a hydrogen atom; and a platinum group metal catalyst (A2), The polysiloxane (A1) is a siloxane unit (Q' unit) represented by SiO2, R 1 'R 2 'R 3 'SiO 1 / 2 Siloxane unit (M' unit) represented by R 4 'R 5 'SiO 2 / 2 Siloxane units (D' units) represented by the formula 6 'SiO 3 / 2 The polyorganosiloxane (a1) (the R 1 '~R 6 Each of R ′ is a group bonded to a silicon atom, and each of them independently represents an alkyl group or an alkenyl group. 1 '~R 6 At least one of R′ is the alkenyl group. 1 "R 2 "R 3 "SiO 1 / 2 Siloxane unit (M” unit) represented by R 4 "R 5 "SiO 2 / 2 Siloxane units (D" units) represented by the formula 6 "SiO 3 / 2 and at least one unit selected from the group consisting of the M″ unit, the D″ unit and the T″ unit. 1 ”~R 6 " are groups or atoms bonded to a silicon atom, and each independently represents an alkyl group or a hydrogen atom. 1 ”~R 6 " at least one of is a hydrogen atom, 12. A laminate comprising a first substrate made of a semiconductor forming substrate, a second substrate made of a support substrate that transmits laser light, and an adhesive layer, a laminate, wherein the adhesive layer is a cured film obtained from any one of the photoirradiation peelable adhesive compositions 1 to 11; 13. A first step of applying any one of the light-irradiation peelable adhesive compositions 1 to 11 to a surface of the first substrate or the second substrate to form an adhesive coating layer; a second step of bonding the first substrate and the second substrate via the adhesive coating layer, applying a load in a thickness direction of the first substrate and the second substrate while performing at least one of a heat treatment and a decompression treatment, thereby bonding the first substrate, the adhesive coating layer, and the second substrate together, and then performing a post-heat treatment; 14. A peeling method comprising irradiating a laser from the second substrate side of the laminate obtained by the laminate manufacturing method according to 13, and peeling off the second substrate. 15. The peeling method according to 14, wherein the wavelength of the laser is 190 nm to 600 nm. to provide. Effect of the Invention

[0014] The specific light-absorbing organic compound used in the present invention, particularly thioindigo derivatives and isothioindigo derivatives, which have the advantages of being relatively inexpensive and showing high solubility in organic solvents, have good light-absorbing ability, so that by mixing this with an adhesive component, a composition can be easily prepared that provides a thin film suitable as a light-irradiation peelable adhesive layer that adheres well between a support and a workpiece such as a wafer when the workpiece is being processed, and that absorbs lasers well after processing, reducing the adhesive strength and allowing peeling. Therefore, by using the light-irradiation peelable adhesive composition of the present invention, an adhesive layer that can be peeled off by laser can be produced without applying an excessive load for peeling to a support, wafer, or other workpiece.

[0015] The laminate of the present invention comprises a first substrate made of a semiconductor forming substrate, a second substrate made of a laser-transparent supporting substrate, and an adhesive layer made of a cured film obtained from the light irradiation peelable adhesive composition having the above-described characteristics. Therefore, the second substrate and the adhesive layer can be easily peeled off by irradiating the adhesive layer with a laser from the second substrate side. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will now be described in more detail. The adhesive composition for peeling off upon light irradiation of the present invention can be used, for example, to form an adhesive layer that is peelably bonded between a support and a circuit surface of a wafer and is used for processing the back surface of the wafer, and contains an adhesive component (S) and a light-absorbing organic compound (X), and the light-absorbing organic compound (X) contains, in the molecule, one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more groups selected from a carbonyl group and a thiocarbonyl group.

[0017] In a preferred embodiment, the light-absorbing organic compound (X) contained in the light-irradiation peelable adhesive composition of the present invention contains one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more carbonyl or thiocarbonyl groups in the molecule.

[0018] The adhesive composition for peeling by light irradiation of the present invention forms an adhesive layer that can be peeled off by irradiation with a laser. Since the adhesive layer contains the light-absorbing organic compound (X), it absorbs the laser favorably and the adhesive strength decreases, and therefore has the advantage that it can be peeled off without applying an excessive load for peeling to a support, a wafer, etc.

[0019] The support and the wafer are temporarily bonded by an adhesive layer obtained from the adhesive composition for peeling off by light irradiation of the present invention, and the back surface of the wafer opposite the circuit surface can be processed by polishing or the like to thin the wafer.

[0020] The laminate of the present invention comprises a first substrate made of a semiconductor forming substrate, a second substrate made of a supporting substrate that transmits laser light, and an adhesive layer made of a cured film formed using the adhesive composition for peeling by light irradiation, and an arbitrary functional layer that transmits or does not transmit laser light may be provided between the substrate and the adhesive layer. In this case, the functional layer is appropriately selected so as not to inhibit peeling by laser irradiation.

[0021] In a preferred embodiment of the present invention, the laminate of the present invention comprises a first substrate comprising a semiconductor forming substrate, a second substrate comprising a laser-transmitting supporting substrate, and an adhesive layer comprising a cured film formed using the photoirradiation-peelable adhesive composition between and in contact with both of these two substrates.

[0022] The laminate of the present invention can be peeled off by irradiating a laser from the side of the second substrate through which the laser transmits, without applying an excessive load for peeling.

[0023] The wavelength of such a laser is usually 190 nm to 600 nm, but from the viewpoint of suitable peeling with good reproducibility, it is preferably 250 nm or more, more preferably 300 nm or more, and preferably 580 nm or less, more preferably 560 nm or less. For example, the laminate of the present invention can be suitably peeled off by a laser having a wavelength of 308 nm, 355 nm, or 532 nm.

[0024] In the present invention, the second substrate must be capable of transmitting the laser irradiated for peeling, but this is not limited to the case where light irradiation is possible from the first substrate side.

[0025] Here, peelable means that the adhesive strength is lower than other locations, i.e., that the adhesive has excellent releasability and is easy to peel off. However, the adhesive layer obtained using the photoirradiation peelable adhesive composition of the present invention has a significantly reduced adhesive strength upon laser irradiation compared to before irradiation.

[0026] In other words, the adhesive layer obtained from the photoirradiation peelable adhesive composition of the present invention effectively bonds, for example, a first substrate made of a wafer to a second substrate made of a laser-transparent supporting substrate while the wafer is being processed, such as thinned, and can be easily peeled off or removed by laser irradiation after processing is completed.

[0027] The light-absorbing organic compound (X) contained in the light-irradiation peelable adhesive composition of the present invention contains one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more selected from a carbonyl group and a thiocarbonyl group in the molecule, preferably contains one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more carbonyl groups or thiocarbonyl groups in the molecule, and more preferably contains two or more aromatic rings, two or more rings containing a heteroatom as a ring-constituting atom, and two or more carbonyl groups or thiocarbonyl groups in the molecule. In this case, the light-absorbing organic compound (X) may contain only one of a carbonyl group and a thiocarbonyl group, or may contain both.

[0028] The number of carbon atoms in the aromatic ring is not particularly limited, but is usually 6 to 30, preferably 20 or less, and more preferably 10 or less. Specific examples of the aromatic ring include, but are not limited to, a benzene ring, a naphthalene ring, and an anthracene ring.

[0029] The ring containing a heteroatom as a ring-constituting atom is not particularly limited as long as it has a cyclic structure and contains a heteroatom such as an oxygen atom, a sulfur atom, or a nitrogen atom as an atom constituting the ring, and may be either an aromatic ring or a non-aromatic ring. The ring containing a heteroatom as a ring-constituting atom is usually a 4- to 10-membered ring, preferably a 4- to 6-membered ring, and more preferably a 5-membered ring, and the number of heteroatoms contained as ring-constituting atoms is usually 1 to 3, preferably 1 to 2, and more preferably 1, and the other ring-constituting atoms are carbon atoms.

[0030] The molecular weight of the light-absorbing organic compound (X) is not particularly limited as long as it exhibits good compatibility with other components, but is usually 5,000 or less. From the viewpoint of ensuring the solubility of the compound in organic solvents and reproducibly obtaining a composition with excellent uniformity, the molecular weight is preferably 2,500 or less, more preferably 1,000 or less, even more preferably 700 or less, and even more preferably 600 or less. From the viewpoint of suppressing sublimation of the compound due to heating or reduced pressure during lamination and thereby suppressing contamination in the system, the molecular weight is preferably 50 or more, more preferably 100 or more, even more preferably 200 or more, and even more preferably 250 or more.

[0031] The light-absorbing organic compound (X) is usually 1.013 x 10 5 It is a solid or liquid at 1 Pa, preferably a solid.

[0032] In a preferred embodiment of the present invention, in the light-absorbing organic compound (X), the aromatic ring and the ring containing a heteroatom as a ring-constituting atom are condensed.

[0033] In a preferred embodiment of the present invention, in the light-absorbing organic compound (X), the carbon atom of the carbonyl group or thiocarbonyl group is a ring-constituting atom of a ring that contains a heteroatom as a ring-constituting atom.

[0034] In a preferred embodiment of the present invention, when a carbon atom of a carbonyl group or a thiocarbonyl group in the light absorbing organic compound (X) is a ring-constituting atom of a ring containing a heteroatom as a ring-constituting atom, the number of such carbonyl groups or thiocarbonyl groups per ring containing a heteroatom as a ring-constituting atom is usually 1 to 3, preferably 1 to 2, and more preferably 1.

[0035] In a preferred embodiment of the present invention, the number of carbonyl or thiocarbonyl groups having a carbon atom that is not a ring member of a ring that contains a heteroatom as a ring member is preferably 3 or less, more preferably 2 or less, even more preferably 1 or less, and still more preferably 0.

[0036] In a preferred embodiment of the present invention, the light-absorbing organic compound (X) is represented by formula (T1-1) or (T2-1).

[0037] [ka]

[0038] X 1 ~X 4 are carbon atoms constituting an aromatic ring, and are each independently bonded to a hydrogen atom, a halogen atom or an organic group other than the carbon atom constituting the aromatic ring; X 5 represents a heteroatom such as an oxygen atom, a sulfur atom, or a nitrogen atom, and X 5 When is a nitrogen atom, it is bonded to a hydrogen atom or an organic group in addition to the carbon atoms constituting the ring.

[0039] The light absorbing organic compound (X) is preferably a thioindigo derivative or an isothioindigo derivative, and more preferably a thioindigo derivative or an isothioindigo derivative represented by formula (T1-2) or (T2-2).

[0040] [ka]

[0041] Each R A are atoms or groups substituted on the benzene ring, and each independently represents a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or an aryl group.

[0042] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom, with a chlorine atom being preferred.

[0043] The alkyl group may be linear, branched, or cyclic, but is preferably a linear or branched alkyl group. The number of carbon atoms is not particularly limited, but is usually 1 to 40, preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less.

[0044] Specific examples of linear or branched alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, and 3-methyl-n-pentyl. Examples of the aryl group include, but are not limited to, a 4-methyl-n-pentyl group, a 1,1-dimethyl-n-butyl group, a 1,2-dimethyl-n-butyl group, a 1,3-dimethyl-n-butyl group, a 2,2-dimethyl-n-butyl group, a 2,3-dimethyl-n-butyl group, a 3,3-dimethyl-n-butyl group, a 1-ethyl-n-butyl group, a 2-ethyl-n-butyl group, a 1,1,2-trimethyl-n-propyl group, a 1,2,2-trimethyl-n-propyl group, a 1-ethyl-1-methyl-n-propyl group, and a 1-ethyl-2-methyl-n-propyl group. Of these, a methyl group is preferred.

[0045] Specific examples of the cyclic alkyl group include a cyclopropyl group, a cyclobutyl group, a 1-methyl-cyclopropyl group, a 2-methyl-cyclopropyl group, a cyclopentyl group, a 1-methyl-cyclobutyl group, a 2-methyl-cyclobutyl group, a 3-methyl-cyclobutyl group, a 1,2-dimethyl-cyclopropyl group, a 2,3-dimethyl-cyclopropyl group, a 1-ethyl-cyclopropyl group, a 2-ethyl-cyclopropyl group, a cyclohexyl group, a 1-methyl-cyclopentyl group, a 2-methyl-cyclopentyl group, a 3-methyl-cyclopentyl group, a 1-ethyl-cyclobutyl group, a 2-ethyl-cyclobutyl group, a 3-ethyl-cyclobutyl group, a 1,2-dimethyl-cyclobutyl group, a 1,3-dimethyl-cyclobutyl group, a 2,2-dimethyl-cyclobutyl group, a 2,3-dimethyl-cyclobutyl group, a 2,4-dimethyl cycloalkyl groups such as aryl-cyclobutyl group, 3,3-dimethyl-cyclobutyl group, 1-n-propyl-cyclopropyl group, 2-n-propyl-cyclopropyl group, 1-i-propyl-cyclopropyl group, 2-i-propyl-cyclopropyl group, 1,2,2-trimethyl-cyclopropyl group, 1,2,3-trimethyl-cyclopropyl group, 2,2,3-trimethyl-cyclopropyl group, 1-ethyl-2-methyl-cyclopropyl group, 2-ethyl-1-methyl-cyclopropyl group, 2-ethyl-2-methyl-cyclopropyl group, and 2-ethyl-3-methyl-cyclopropyl group; and bicycloalkyl groups such as bicyclobutyl group, bicyclopentyl group, bicyclohexyl group, bicycloheptyl group, bicyclooctyl group, bicyclononyl group, and bicyclodecyl group, but are not limited to these.

[0046] The alkenyl group may be either linear or branched, and the number of carbon atoms therein is not particularly limited, but is usually 2 to 40, preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less.

[0047] Specific examples of the alkenyl group include ethenyl, 1-propenyl, 2-propenyl, 1-methyl-1-ethenyl, 1-butenyl, 2-butenyl, 3-butenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-ethylethenyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-n-propylethenyl, 1-methyl-1-butenyl, 1-methyl-2-butenyl, 1-methyl-3-butenyl, 2-ethyl-2- propenyl, 2-methyl-1-butenyl, 2-methyl-2-butenyl, 2-methyl-3-butenyl, 3-methyl-1-butenyl, 3-methyl-2-butenyl, 3-methyl-3-butenyl, 1,1-dimethyl-2-propenyl, 1-i-propylethenyl, 1,2-dimethyl-1-propenyl, 1,2-dimethyl-2-propenyl, 1-cyclopentenyl, 2-cyclopentenyl, 3-cyclopentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, 5-hexenyl, 1-methyl-1- pentenyl group, 1-methyl-2-pentenyl group, 1-methyl-3-pentenyl group, 1-methyl-4-pentenyl group, 1-n-butylethenyl group, 2-methyl-1-pentenyl group, 2-methyl-2-pentenyl group, 2-methyl-3-pentenyl group, 2-methyl-4-pentenyl group, 2-n-propyl-2-propenyl group, 3-methyl-1-pentenyl group, 3-methyl-2-pentenyl group, 3-methyl-3-pentenyl group, 3-methyl-4-pentenyl group, 3-ethyl-3-butenyl group, 4-methyl-1-pentenyl group, 4-methyl-2-pentenyl group, 4 -Methyl-3-pentenyl, 4-methyl-4-pentenyl, 1,1-dimethyl-2-butenyl, 1,1-dimethyl-3-butenyl, 1,2-dimethyl-1-butenyl, 1,2-dimethyl-2-butenyl, 1,2-dimethyl-3-butenyl, 1-methyl-2-ethyl-2-propenyl, 1-s-butylethenyl, 1,3-dimethyl-1-butenyl, 1,3-dimethyl-2-butenyl, 1,3-dimethyl-3-butenyl, 1-i-butylethenyl, 2,2-dimethyl-3-butenyl, 2,3-dimethyl-1-butenyl, 2,3-dimethyl-2-butenyl group, 2,3-dimethyl-3-butenyl group, 2-i-propyl-2-propenyl group, 3,3-dimethyl-1-butenyl group, 1-ethyl-1-butenyl group, 1-ethyl-2-butenyl group, 1-ethyl-3-butenyl group, 1-n-propyl-1-propenyl group, 1-n-propyl-2-propenyl group, 2-ethyl-1-butenyl group, 2-ethyl-2-butenyl group, 2-ethyl-3-butenyl group, 1,1,2-trimethyl-2-propenyl group, 1-t-butylethenyl group, 1-methyl-1-ethyl-2-propenyl group, 1-ethyl-2-methyl-1-propenyl group, 1-ethyl-2-methyl-2-propenyl group, 1-i-propyl-1-propenyl group, 1-i-propyl- Examples of the cyclopentyl group include, but are not limited to, a 2-propenyl group, a 1-methyl-2-cyclopentenyl group, a 1-methyl-3-cyclopentenyl group, a 2-methyl-1-cyclopentenyl group, a 2-methyl-2-cyclopentenyl group, a 2-methyl-3-cyclopentenyl group, a 2-methyl-4-cyclopentenyl group, a 2-methyl-5-cyclopentenyl group, a 2-methylene-cyclopentyl group, a 3-methyl-1-cyclopentenyl group, a 3-methyl-2-cyclopentenyl group, a 3-methyl-3-cyclopentenyl group, a 3-methyl-4-cyclopentenyl group, a 3-methyl-5-cyclopentenyl group, a 3-methylene-cyclopentyl group, a 1-cyclohexenyl group, a 2-cyclohexenyl group, and a 3-cyclohexenyl group. Of these, ethenyl and 2-propenyl groups are preferred.

[0048] The alkynyl group may be either linear or branched, and the number of carbon atoms therein is not particularly limited, but is usually 2 to 40, preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less.

[0049] Specific examples of alkynyl groups include ethynyl, n-1-propynyl, n-2-propynyl, n-1-butynyl, n-2-butynyl, n-3-butynyl, 1-methyl-2-propynyl, n-1-pentynyl, n-2-pentynyl, n-3-pentynyl, n-4-pentynyl, 1-methyl-n-butynyl, 2-methyl-n-butynyl, 3-methyl-n-butynyl, 1,1-dimethyl-n-propynyl, n-1-hexynyl, n-1-decynyl, n-1-pentadecinyl, and n-1-eicosynyl.

[0050] The aryl group may be any of a phenyl group, a monovalent group derived by removing one hydrogen atom from a fused-ring aromatic hydrocarbon compound, and a monovalent group derived by removing one hydrogen atom from a ring-linked aromatic hydrocarbon compound, and the number of carbon atoms therein is not particularly limited, but is usually 40 or less, preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less, with the lower limit being 6.

[0051] Specific examples of the aryl group include, but are not limited to, a phenyl group, a 1-naphthyl group, a 2-naphthyl group, a 1-anthryl group, a 2-anthryl group, a 9-anthryl group, a 1-phenanthryl group, a 2-phenanthryl group, a 3-phenanthryl group, a 4-phenanthryl group, a 9-phenanthryl group, a 1-naphthacenyl group, a 2-naphthacenyl group, a 5-naphthacenyl group, a 2-chrysenyl group, a 1-pyrenyl group, a 2-pyrenyl group, a pentacenyl group, a benzopyrenyl group, a triphenylenyl group, a biphenyl-2-yl group, a biphenyl-3-yl group, a biphenyl-4-yl group, a paraterphenyl-4-yl group, a metaterphenyl-4-yl group, an orthoterphenyl-4-yl group, a 1,1'-binaphthyl-2-yl group, and a 2,2'-binaphthyl-1-yl group. Among these, R A is preferably a halogen atom or an alkyl group.

[0052] a to d each independently represent an integer of 0 to 4, preferably 3 or less, more preferably 2 or less.

[0053] In a more preferred embodiment of the present invention, the thioindigo derivative or isothioindigo derivative used in the present invention is represented by formula (T1-3) or (T2-3).

[0054] [ka]

[0055] Each R B and each R C each independently represents a hydrogen atom, a halogen atom or an alkyl group, and specific examples of the halogen atom and the alkyl group are the same as those mentioned above.

[0056] Preferably, in each of formulas (T1-3) and (T2-3), two R B are the same atom or group, and two R C are the same atom or group.

[0057] In the present invention, from the viewpoint of obtaining the effects of the present invention with even better reproducibility, thioindigo derivatives are preferred.

[0058] Specific examples of thioindigo derivatives or isothioindigo derivatives are listed below, but the invention is not limited thereto.

[0059] [ka]

[0060] The adhesive component (S) contained in the adhesive composition for peeling off by light irradiation of the present invention can be any of various compounds used as adhesive components in this type of composition, as long as it has adhesive properties. Examples of such compounds include siloxane-based resins, hydrocarbon resins, acrylic-styrene-based, maleimide-based resins, and combinations of these. Among these, siloxane-based resins are preferred.

[0061] In a preferred embodiment of the present invention, the photoirradiation peelable adhesive composition of the present invention contains, as the adhesive component (S), a component (A) that cures via a hydrosilylation reaction.

[0062] In a more preferred embodiment of the present invention, the component (A) that cures by a hydrosilylation reaction contains siloxane units (Q units) represented by SiO2, R 1 R 2 R 3 SiO 1 / 2 Siloxane unit (M unit) represented by R 4 R 5 SiO 2 / 2 Siloxane units (D units) represented by the formula 6 SiO 3 / 2 and a platinum group metal catalyst (A2), wherein the polysiloxane (A1) contains one or more units selected from the group consisting of siloxane units (T units) represented by SiO2, siloxane units (Q' units) represented by R 1 'R 2 'R 3 'SiO 1 / 2 Siloxane unit (M' unit) represented by R 4 'R 5 'SiO 2 / 2 Siloxane units (D' units) represented by the formula 6 'SiO 3 / 2 and at least one unit selected from the group consisting of M' units, D' units and T' units; and a polyorganosiloxane (a1) having siloxane units (Q" units) represented by SiO2, R 1 "R 2 "R 3 "SiO 1 / 2 Siloxane unit (M” unit) represented by R 4 "R 5 "SiO 2 / 2 Siloxane units (D" units) represented by the formula 6 "SiO 3 / 2and a polyorganosiloxane (a2) containing one or more units selected from the group consisting of siloxane units (T″ units) represented by the following formula:

[0063] R 1 ~R 6 are groups or atoms bonded to a silicon atom, and each independently represents an alkyl group, an alkenyl group, or a hydrogen atom. Specific examples and preferred conditions for the alkyl group and alkenyl group are the same as those mentioned above.

[0064] R 1 '~R 6 R ′ is a group bonded to a silicon atom, and each independently represents an alkyl group or an alkenyl group. 1 '~R 6 At least one of is an alkenyl group.

[0065] R 1 ”~R 6 " are groups or atoms bonded to the silicon atom, and each independently represents an alkyl group or a hydrogen atom, but R 1 ”~R 6 At least one of " is a hydrogen atom.

[0066] As described above, the polysiloxane (A1) contains the polyorganosiloxane (a1) and the polyorganosiloxane (a2), and the alkenyl group contained in the polyorganosiloxane (a1) and the hydrogen atom (Si-H group) contained in the polyorganosiloxane (a2) form a crosslinked structure through a hydrosilylation reaction in the presence of a platinum group metal catalyst (A2), thereby curing.

[0067] The polyorganosiloxane (a1) contains one or more units selected from the group consisting of Q' units, M' units, D' units and T' units, and also contains at least one unit selected from the group consisting of M' units, D' units and T' units. As the polyorganosiloxane (a1), a combination of two or more polyorganosiloxanes satisfying such conditions may be used.

[0068] Preferred combinations of two or more selected from the group consisting of Q' units, M' units, D' units and T' units include, but are not limited to, (Q' units and M' units), (D' units and M' units), (T' units and M' units) and (Q' units, T' units and M' units).

[0069] In addition, when the polyorganosiloxane (a1) contains two or more types of polyorganosiloxanes, combinations of (Q' units and M' units) and (D' units and M' units), combinations of (T' units and M' units) and (D' units and M' units), and combinations of (Q' units, T' units and M' units) and (T' units and M' units) are preferred, but are not limited to these.

[0070] The polyorganosiloxane (a2) contains one or more units selected from the group consisting of Q″ units, M″ units, D″ units, and T″ units, and also contains at least one unit selected from the group consisting of M″ units, D″ units, and T″ units. As the polyorganosiloxane (a2), a combination of two or more polyorganosiloxanes satisfying such conditions may be used.

[0071] Preferred combinations of two or more selected from the group consisting of Q″ units, M″ units, D″ units and T″ units include, but are not limited to, (M″ units and D″ units), (Q″ units and M″ units), and (Q″ units, T″ units and M″ units).

[0072] The polyorganosiloxane (a1) is composed of siloxane units having alkyl and / or alkenyl groups bonded to the silicon atoms thereof. 1 '~R 6 The proportion of alkenyl groups in all the substituents represented by R 1 '~R 6 ' can be an alkyl group.

[0073] The polyorganosiloxane (a2) is composed of siloxane units in which an alkyl group and / or a hydrogen atom is bonded to the silicon atom. 1 ”~R 6 The proportion of hydrogen atoms in all the substituents and substituted atoms represented by R 1 ”~R 6 " can be an alkyl group.

[0074] The polysiloxane (A1) contains a polyorganosiloxane (a1) and a polyorganosiloxane (a2). In a preferred embodiment of the present invention, the molar ratio of the alkenyl groups contained in the polyorganosiloxane (a1) to the hydrogen atoms constituting the Si-H bonds contained in the polyorganosiloxane (a2) can be in the range of 1.0:0.5 to 1.0:0.66.

[0075] The weight average molecular weight of each of the polyorganosiloxane (a1) and the polyorganosiloxane (a2) is usually from 500 to 1,000,000, and preferably from 5,000 to 50,000.

[0076] The weight average molecular weight in the present invention can be measured, for example, by using a GPC apparatus (EcoSEC, HLC-8320GPC, manufactured by Tosoh Corporation) and a GPC column (Shodex (registered trademark), KF-803L, KF-802, and KF-801, manufactured by Showa Denko K.K.), setting the column temperature to 40° C., using tetrahydrofuran as an eluent (elution solvent), setting the flow rate (flow velocity) to 1.0 mL / min, and using polystyrene (manufactured by Sigma-Aldrich Co.) as a standard sample.

[0077] The polyorganosiloxane (a1) and the polyorganosiloxane (a2) contained in the photoirradiation peelable adhesive composition of the present invention react with each other by hydrosilylation reaction to form a cured film. Therefore, the mechanism of the curing is different from that via, for example, a silanol group, and therefore, neither siloxane needs to contain a functional group that forms a silanol group by hydrolysis, such as a silanol group or an alkyloxy group.

[0078] In a preferred embodiment of the present invention, component (A) contains a platinum group metal catalyst (A2) together with the above-mentioned polysiloxane (A1). Such a platinum-based metal catalyst is a catalyst for promoting the hydrosilylation reaction between the alkenyl groups of the polyorganosiloxane (a1) and the Si-H groups of the polyorganosiloxane (a2).

[0079] Specific examples of platinum-based metal catalysts include platinum black, platinic chloride, chloroplatinic acid, a reaction product of chloroplatinic acid with a monohydric alcohol, a complex of chloroplatinic acid with an olefin, platinum bisacetoacetate, and other platinum-based catalysts, but are not limited to these.

[0080] An example of a complex of platinum with an olefin is, but is not limited to, a complex of divinyltetramethyldisiloxane with platinum.

[0081] The amount of the platinum group metal catalyst (A2) is usually in the range of 1.0 to 50.0 ppm based on the total amount of the polyorganosiloxane (a1) and the polyorganosiloxane (a2).

[0082] Component (A) may contain a polymerization inhibitor (A3). By including a polymerization inhibitor in the photoirradiation peelable adhesive composition of the present invention, it becomes possible to suitably control the curing caused by heating during lamination, and it is possible to reproducibly obtain a composition that gives an adhesive layer with excellent adhesion and peelability.

[0083] The polymerization inhibitor is not particularly limited as long as it can inhibit the progress of the hydrosilylation reaction. Specific examples include, but are not limited to, alkynylalkyl alcohols such as 1-ethynyl-1-cyclohexanol.

[0084] The amount of the polymerization inhibitor is usually 1000.0 ppm or more based on the polyorganosiloxane (a1) and the polyorganosiloxane (a2) from the viewpoint of obtaining the effect thereof, and is 10000.0 ppm or less from the viewpoint of preventing excessive inhibition of the hydrosilylation reaction.

[0085] The adhesive composition for peeling off by light irradiation of the present invention may contain component (B) containing at least one selected from the group consisting of a component containing an epoxy-modified polyorganosiloxane, a component containing a methyl group-containing polyorganosiloxane, and a component containing a phenyl group-containing polyorganosiloxane. By including such component (B) in the adhesive composition for peeling off by light irradiation of the present invention, the obtained adhesive layer can be peeled off with good reproducibility. Among these, a component containing a methyl group-containing polyorganosiloxane is preferred.

[0086] Examples of epoxy-modified polyorganosiloxane include R 11 R 12 SiO 2 / 2 The siloxane unit (D 10 Examples include those containing the unit.

[0087] R 11 is a group bonded to a silicon atom and represents an alkyl group; R 12 is a group bonded to a silicon atom, and represents an epoxy group or an organic group containing an epoxy group. Specific examples of the alkyl group include those listed above.

[0088] Furthermore, the epoxy group in the organic group containing an epoxy group may be an independent epoxy group that is not condensed with other rings, or may be an epoxy group that forms a condensed ring with other rings, such as a 1,2-epoxycyclohexyl group.

[0089] Specific examples of organic groups containing an epoxy group include, but are not limited to, 3-glycidoxypropyl and 2-(3,4-epoxycyclohexyl)ethyl.

[0090] In the present invention, a preferred example of the epoxy-modified polyorganosiloxane is epoxy-modified polydimethylsiloxane, but is not limited thereto.

[0091] The epoxy-modified polyorganosiloxane is a polyorganosiloxane having the above-mentioned siloxane unit (D 10 D 10 In addition to the units, the above-mentioned Q units, M units and / or T units may be contained.

[0092] In a preferred embodiment of the present invention, specific examples of the epoxy-modified polyorganosiloxane include D 10 Polyorganosiloxane consisting of only units, D 10 Polyorganosiloxanes containing D units and Q units; 10 Polyorganosiloxanes containing D units and M units; 10 Polyorganosiloxanes containing D units and T units; 10 Polyorganosiloxanes containing units, Q units and M units, D 10 Polyorganosiloxanes containing units, M units and T units, D 10 and polyorganosiloxanes containing Q units, M units and T units.

[0093] The epoxy-modified polyorganosiloxane is preferably an epoxy-modified polydimethylsiloxane having an epoxy value of 0.1 to 5, and its weight average molecular weight is usually 1,500 to 500,000, but from the viewpoint of suppressing precipitation in the composition, it is preferably 100,000 or less.

[0094] Specific examples of epoxy-modified polyorganosiloxanes include CMS-227 (manufactured by Gelest Co., Ltd., weight average molecular weight 27,000) represented by formula (A-1), ECMS-327 (manufactured by Gelest Co., Ltd., weight average molecular weight 28,800) represented by formula (A-2), KF-101 (manufactured by Shin-Etsu Chemical Co., Ltd., weight average molecular weight 31,800) represented by formula (A-3), and KF-1001 (manufactured by Shin-Etsu Chemical Co., Ltd., weight average molecular weight 55,600) represented by formula (A-4). Examples of the polyimide copolymer include, but are not limited to, trade name KF-1005 (manufactured by Shin-Etsu Chemical Co., Ltd., weight average molecular weight 11,500) represented by formula (A-5), trade name X-22-343 (manufactured by Shin-Etsu Chemical Co., Ltd., weight average molecular weight 2,400) represented by formula (A-6), trade name BY16-839 (manufactured by Dow Corning Corporation, weight average molecular weight 51,700) represented by formula (A-7), and trade name ECMS-327 (manufactured by Gelest Pharmaceuticals, weight average molecular weight 28,800) represented by formula (A-8).

[0095] [ka] (m and n are the numbers of repeating units.)

[0096] [ka] (m and n are the numbers of repeating units.)

[0097] [ka] (m and n are the numbers of repeating units, and R is an alkylene group having 1 to 10 carbon atoms.)

[0098] [ka] (m and n are the numbers of repeating units, and R is an alkylene group having 1 to 10 carbon atoms.)

[0099] [ka] (m, n, and o are the numbers of repeating units, and R is an alkylene group having 1 to 10 carbon atoms.)

[0100] [ka] (m and n are the numbers of repeating units, and R is an alkylene group having 1 to 10 carbon atoms.)

[0101] [ka] (m and n are the numbers of repeating units, and R is an alkylene group having 1 to 10 carbon atoms.)

[0102] [ka] (m and n are the numbers of repeating units.)

[0103] Examples of the methyl group-containing polyorganosiloxane include R 210 R 220 SiO 2 / 2 The siloxane unit (D 200 units), preferably R 21 R 21 SiO 2 / 2 The siloxane unit (D 20 Examples include those containing the unit.

[0104] R 210 and R 220 are groups bonded to a silicon atom, and each independently represents an alkyl group, with at least one being a methyl group. Specific examples of the alkyl group include those listed above. R 21 is a group bonded to a silicon atom, and represents an alkyl group. Specific examples of the alkyl group include those listed above. 21 As the alkyl group, a methyl group is preferable.

[0105] In the present invention, a preferred example of the methyl group-containing polyorganosiloxane is polydimethylsiloxane, but is not limited thereto.

[0106] The methyl group-containing polyorganosiloxane is a polyorganosiloxane having the above-mentioned siloxane unit (D 200 Unit or D 20 D 200 Unit or D 20 In addition to the units, the above-mentioned Q units, M units and / or T units may be contained.

[0107] In one embodiment of the present invention, specific examples of the methyl group-containing polyorganosiloxane include D 200 Polyorganosiloxane consisting of only units, D 200 Polyorganosiloxanes containing D units and Q units; 200 Polyorganosiloxanes containing D units and M units; 200 Polyorganosiloxanes containing D units and T units; 200 Polyorganosiloxanes containing units, Q units and M units, D 200 Polyorganosiloxanes containing units, M units and T units, D 200 Examples of suitable polyorganosiloxanes include polyorganosiloxanes containing Q, M, and T units.

[0108] In a preferred embodiment of the present invention, specific examples of the methyl group-containing polyorganosiloxane include D 20 Polyorganosiloxane consisting of only units, D 20 Polyorganosiloxanes containing D units and Q units; 20 Polyorganosiloxanes containing D units and M units; 20 Polyorganosiloxanes containing D units and T units; 20 Polyorganosiloxanes containing units, Q units and M units, D 20 Polyorganosiloxanes containing units, M units and T units, D 20 Examples of suitable polyorganosiloxanes include polyorganosiloxanes containing Q, M, and T units.

[0109] The viscosity of methyl group-containing polyorganosiloxane is usually 1,000 to 2,000,000 mm 2 / s, but preferably 10,000 to 1,000,000 mm 2 / s. The methyl group-containing polyorganosiloxane is typically a dimethyl silicone oil made of polydimethylsiloxane. This viscosity value is indicated as a kinetic viscosity, and is expressed as centistokes (cSt) = mm 2 / s. Kinematic viscosity can be measured with a kinematic viscometer. Viscosity (mPa s) can also be converted to density (g / cm 3 It can also be calculated by dividing by the viscosity (mm 2 / s) = viscosity (mPa s) / density (g / cm 3 ) can be calculated from the formula:

[0110] Specific examples of methyl group-containing polyorganosiloxanes include WACKER (registered trademark) SILICONE FLUID AK series manufactured by Wacker Co., Ltd., dimethyl silicone oils (KF-96L, KF-96A, KF-96, KF-96H, KF-69, KF-965, KF-968) and cyclic dimethyl silicone oil (KF-995) manufactured by Shin-Etsu Chemical Co., Ltd., but are not limited to these.

[0111] Examples of the phenyl group-containing polyorganosiloxane include R 31 R 32 SiO 2 / 2 The siloxane unit (D 30 Examples include those containing the unit.

[0112] R 31 is a group bonded to a silicon atom and represents a phenyl group or an alkyl group; R 32 is a group bonded to a silicon atom and represents a phenyl group. Specific examples of the alkyl group include those listed above, with a methyl group being preferred.

[0113] The phenyl group-containing polyorganosiloxane is a polyorganosiloxane having the above-mentioned siloxane unit (D 30 D 30 In addition to the units, the above-mentioned Q units, M units and / or T units may be contained.

[0114] In a preferred embodiment of the present invention, specific examples of the phenyl group-containing polyorganosiloxane include D 30 Polyorganosiloxane consisting of only units, D 30 Polyorganosiloxanes containing D units and Q units; 30 Polyorganosiloxanes containing D units and M units; 30 Polyorganosiloxanes containing D units and T units; 30 Polyorganosiloxanes containing units, Q units and M units, D 30 Polyorganosiloxanes containing units, M units and T units, D 30 Examples of suitable polyorganosiloxanes include polyorganosiloxanes containing Q, M, and T units.

[0115] The weight average molecular weight of the phenyl group-containing polyorganosiloxane is usually 1,500 to 500,000, but from the viewpoint of inhibiting precipitation in the composition, it is preferably 100,000 or less.

[0116] A specific example of the phenyl group-containing polyorganosiloxane is PMM-1043 (trade name, manufactured by Gelest, Inc., weight average molecular weight 67,000, viscosity 30,000 mm), represented by formula (C-1). 2 / s), and PMM-1025 (trade name, manufactured by Gelest, Inc., weight average molecular weight 25,200, viscosity 500 mm 2 / s), the trade name KF50-3000CS (manufactured by Shin-Etsu Chemical Co., Ltd., weight average molecular weight 39,400, viscosity 3000 mm 2 / s), and the product name TSF431 (manufactured by MOMENTIVE Co., Ltd., weight average molecular weight 1,800, viscosity 100 mm 2 / s), and the product name TSF433 (manufactured by MOMENTIVE, weight average molecular weight 3,000, viscosity 450 mm2 / s), and PDM-0421 (trade name, manufactured by Gelest, Inc., weight average molecular weight 6,200, viscosity 100 mm 2 / s), and PDM-0821 (manufactured by Gelest, Inc., weight average molecular weight 8,600, viscosity 125 mm 2 / s), but are not limited to these.

[0117] [ka] (m and n represent the number of repeating units.)

[0118] [ka] (m and n represent the number of repeating units.)

[0119] [ka] (m and n represent the number of repeating units.)

[0120] [ka] (m and n represent the number of repeating units.)

[0121] [ka] (m and n represent the number of repeating units.)

[0122] [ka] (m and n represent the number of repeating units.)

[0123] [ka] (m and n represent the number of repeating units.)

[0124] The light irradiation peelable adhesive composition of the present invention may contain component (A) and component (B) in any ratio. In consideration of the balance between adhesion and peelability, the ratio of component (A) to component (B) in mass % is preferably 99.995:0.005 to 30:70, and more preferably 99.9:0.1 to 75:25.

[0125] The photoirradiation peelable adhesive composition may contain a solvent for the purpose of adjusting the viscosity, etc., and specific examples thereof include, but are not limited to, aliphatic hydrocarbons, aromatic hydrocarbons, ketones, etc.

[0126] More specifically, examples of the solvent include, but are not limited to, hexane, heptane, octane, nonane, decane, undecane, dodecane, isododecane, menthane, limonene, toluene, xylene, methylene, cumene, MIBK (methyl isobutyl ketone), butyl acetate, diisobutyl ketone, 2-octanone, 2-nonanone, 5-nonanone, etc. Such solvents may be used alone or in combination of two or more.

[0127] When the adhesive composition for peeling off by light irradiation of the present invention contains a solvent, the content of the solvent is appropriately set taking into consideration the desired viscosity of the composition, the coating method to be adopted, the thickness of the thin film to be produced, etc., but is in the range of about 10 to 90 mass % based on the entire composition.

[0128] The light-irradiation peelable adhesive composition of the present invention may further contain silica particles in addition to the above-mentioned components for the purpose of improving peelability.

[0129] Here, the silica particles refer to silicon dioxide particles having an average particle size on the order of nanometers (typically 500 nm or less, preferably 100 nm or less). The particle size is measured using a nitrogen adsorption isotherm according to the BET method.

[0130] The adhesive composition for peeling off by light irradiation of the present invention containing silica particles can be produced using a silicone powder having a predetermined average particle size or a silica sol containing silica having a predetermined average particle size.

[0131] Specific examples of silicone powders include silicone powders KMP series manufactured by Shin-Etsu Chemical Co., Ltd., such as KMP-600, KMP-601, KMP-602, KMP-605, and X-52-7030, but are not limited thereto.

[0132] Specific examples of colloidal silica (silica sol) include MA-ST-S (silica sol dispersed in methanol), MT-ST (silica sol dispersed in methanol), MA-ST-UP (silica sol dispersed in methanol) manufactured by Nissan Chemical Co., Ltd., trade names MA-ST-M (silica sol dispersed in methanol), MA-ST-L (silica sol dispersed in methanol), IPA-ST-S (silica sol dispersed in isopropanol), IPA-ST (silica sol dispersed in isopropanol), IPA-ST-UP (silica sol dispersed in isopropanol), IPA-ST-L (silica sol dispersed in isopropanol), IPA-ST-ZL (silica sol dispersed in isopropanol), NPC-ST-30 (silica sol dispersed in n-propyl cellosolve), and PGM-ST. Examples of silica sol dispersed in 1-methoxy-2-propanol, DMAC-ST (silica sol dispersed in dimethylacetamide), XBA-ST (silica sol dispersed in xylene / n-butanol mixed solvent), trade name EAC-ST (silica sol dispersed in ethyl acetate), PMA-ST (silica sol dispersed in propylene glycol monomethyl ether acetate), MEK-ST (silica sol dispersed in methyl ethyl ketone), MEK-ST-UP (silica sol dispersed in methyl ethyl ketone), MEK-ST-L (silica sol dispersed in methyl ethyl ketone), MIBK-ST (silica sol dispersed in methyl isobutyl ketone), and the like can be mentioned, but are not limited to these.

[0133] When using silica sol to produce the adhesive composition for peeling off by light irradiation of the present invention, the composition can be produced efficiently by using silica sol containing the organic solvent contained in the target final composition as a dispersion medium. At this time, it is also important to note that the concentration of the sol and the amount used must be determined so that the silica particles in the final composition are in the desired amount. In addition, the solvent of the silica sol can be replaced with a desired solvent by solvent replacement according to a standard method.

[0134] When the light-radiation peelable adhesive composition of the present invention contains silica particles, the content thereof is usually 50 mass % or less relative to the adhesive component (S) from the viewpoint of suppressing inhibition of curing of the composition.

[0135] The viscosity of the adhesive composition for peeling off after irradiation of the present invention is usually 1,000 to 5,000 mPa s at 25° C. The viscosity of the adhesive composition for peeling off after irradiation of the present invention can be adjusted by changing the types of organic solvents used, their ratios, the concentrations of film-constituting components, etc., taking into consideration various factors such as the coating method used and the desired film thickness.

[0136] The adhesive composition for peeling off upon light irradiation of the present invention can be produced by mixing the film constituting components and a solvent. However, when no solvent is included, the adhesive composition for peeling off upon light irradiation of the present invention can be produced by mixing the film constituting components. The mixing order is not particularly limited, but an example of a method for easily and reproducibly producing the adhesive composition for peeling off by irradiation of the present invention includes, for example, a method of dissolving all of the film constituents in a solvent, or a method of dissolving a part of the film constituents in a solvent, dissolving the remaining film constituents in a solvent, and mixing the resulting solutions. In this case, if necessary, a part of the solvent or a film constituent with excellent solubility can be added last. When preparing the composition, it may be heated appropriately within a range that does not cause the components to decompose or change in quality.

[0137] In the present invention, the light-irradiation peelable adhesive composition may be filtered using a sub-micrometer filter or the like during the production stage of the composition or after all of the components have been mixed, for the purpose of removing foreign matter in the composition.

[0138] As described above, the laminate of the present invention comprises a first substrate made of a semiconductor forming substrate, a second substrate made of a supporting substrate that transmits laser, and an adhesive layer made of a cured film formed using the adhesive composition for peeling by light irradiation, so the manufacturing method is not particularly limited as long as the adhesive layer made of a cured film is formed using the adhesive composition for peeling by light irradiation. From the viewpoint of realizing the effects of the present invention with good reproducibility, the laser transmittance of the adhesive layer is not particularly limited as long as it can absorb the amount of laser required for peeling, but is preferably 99% or less, more preferably 90% or less, even more preferably 85% or less, and even more preferably 80% or less, and the lower limit is 0% (i.e., the laser is completely absorbed).

[0139] In a preferred embodiment of the present invention, the method for producing a laminate of the present invention includes a first step of applying the adhesive composition for peeling off by light irradiation to the surface of a first substrate or a second substrate to form an adhesive coating layer, and a second step of bonding the first substrate and the second substrate together via the adhesive coating layer, applying a load in the thickness direction of the first substrate and the second substrate while performing at least one of a heat treatment and a decompression treatment, thereby bonding the first substrate, the adhesive coating layer, and the second substrate together, and then performing a post-heat treatment. The post-heat treatment in the second step allows the adhesive coating layer to be finally cured appropriately to become an adhesive layer.

[0140] Here, for example, the first substrate is a wafer and the second substrate is a support, and the adhesive composition for peeling upon light irradiation may be applied to either the first substrate or the second substrate, or to both, but is preferably applied to the first substrate.

[0141] Examples of the wafer include, but are not limited to, silicon wafers and glass wafers with a diameter of about 300 mm and a thickness of about 770 μm.

[0142] The support (carrier) is not particularly limited as long as it transmits the laser, but its transmittance is usually 80% or more, preferably 90% or more. Specifically, for example, a silicon wafer with a diameter of about 300 mm and a thickness of about 700 mm can be mentioned, but is not limited thereto.

[0143] The laser used here refers to a laser used in the peeling step described below, and its wavelength is usually 190 nm to 600 nm, but from the viewpoint of suitable peeling with good reproducibility, it is preferably 250 nm or more, more preferably 300 nm or more, and preferably 580 nm or less, more preferably 560 nm or less. For example, the laminate of the present invention can be suitably peeled off by a laser of 308 nm, 355 nm, or 532 nm.

[0144] The thickness of the adhesive coating layer is usually 5 to 500 μm, but from the viewpoint of maintaining the film strength, it is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, and from the viewpoint of avoiding non-uniformity due to a thick film, it is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 120 μm or less, and even more preferably 70 μm or less.

[0145] The coating method is not particularly limited, but is usually a spin coating method. Note that a method of forming a coating film by a separate spin coating method or the like and attaching a sheet-like coating film may also be adopted, and this method is also referred to as coating or coating film.

[0146] The temperature for the heat treatment of the applied light irradiation peelable adhesive composition varies depending on the film thickness, etc. and cannot be generally specified, but is usually 80° C. or higher, and from the viewpoint of preventing excessive curing, is preferably 150° C. or lower, and the heating time is usually 30 seconds or more, preferably 1 minute or more, from the viewpoint of ensuring the expression of temporary adhesive function, and usually 5 minutes or less, preferably 2 minutes or less, from the viewpoint of suppressing deterioration of the adhesive layer and other members. Heating can be performed using a hot plate, oven, etc.

[0147] The reduced pressure treatment can be carried out by exposing the two substrates and the adhesive coating layer therebetween to an atmospheric pressure of 10 to 10,000 Pa. The reduced pressure treatment time is usually 1 to 30 minutes.

[0148] In a preferred embodiment of the invention, the two substrates and the layer therebetween are laminated together, preferably by heat treatment, more preferably by a combination of heat treatment and reduced pressure treatment.

[0149] The load in the thickness direction of the first substrate and the second substrate is not particularly limited as long as it does not adversely affect the first substrate and the second substrate and the layers therebetween and can firmly adhere them to each other, but is usually within the range of 10 to 1,000 N.

[0150] The post-heating temperature is preferably 120° C. or higher from the viewpoint of obtaining a sufficient curing speed, and is preferably 260° C. or lower from the viewpoint of preventing deterioration of the substrate and adhesive. The heating time is usually 1 minute or more from the viewpoint of realizing suitable bonding of the wafer by curing, and preferably 5 minutes or more from the viewpoint of stabilizing the physical properties of the adhesive, and is usually 180 minutes or less, preferably 120 minutes or less from the viewpoint of avoiding adverse effects on the adhesive layer due to excessive heating. Heating can be performed using a hot plate, oven, etc. One purpose of the post-heating treatment is to more suitably cure the adhesive component (S) containing the component (A) that cures by, for example, a hydrosilylation reaction.

[0151] The peeling method of the present invention is to irradiate a laser from the second substrate side of the laminate of the present invention and remove the second substrate. In the laminate of the present invention, the first substrate and the second substrate that transmits the laser are temporarily bonded to each other in a manner that allows them to be peeled off by a laser-absorbing adhesive layer. When the adhesive layer is irradiated with a laser from the second substrate side, the laser is absorbed and the surface of the adhesive layer is decomposed, and a small amount of gas that does not damage the substrate is generated between the adhesive layer and the second substrate, thereby reducing the adhesive force, and the second substrate can be easily separated from the first substrate and the adhesive layer through the interface between the second substrate and the adhesive layer. Usually, peeling is performed after the laminate of the present invention is manufactured and subjected to a predetermined processing or the like.

[0152] Here, the processing is, for example, processing of the side opposite to the circuit surface of the wafer, and includes thinning the wafer by polishing the back surface of the wafer. Then, through-silicon vias (TSVs) and the like are formed, and then the thinned wafer is peeled off from the support to form a wafer stack, which is then three-dimensionally mounted. Also, before or after this, electrodes and the like are formed on the back surface of the wafer. During the wafer thinning and TSV process, heat of 250 to 350°C is applied while the wafer is attached to the support, and the stack of the present invention, including the adhesive layer, is resistant to this load. In addition, the processing is not limited to the above-mentioned processing, and includes, for example, carrying out a mounting process of a semiconductor component when a substrate for mounting the semiconductor component is temporarily bonded to a support to support the substrate.

[0153] For example, a wafer with a diameter of 300 mm and a thickness of about 770 μm can be thinned to a thickness of about 80 μm to 4 μm by polishing the back side opposite the circuit surface on the front side.

[0154] It is not necessary to irradiate the entire adhesive layer with the laser. Even if the adhesive layer has both irradiated and non-irradiated areas, the adhesive strength of the adhesive layer as a whole is sufficiently reduced, so that the second substrate can be removed from the laminate at the interface between the adhesive layer and the second substrate by, for example, pulling up the second substrate with a slight external force. The ratio and positional relationship between the laser-irradiated and non-irradiated areas vary depending on the type and specific composition of the adhesive used, the thickness of the adhesive layer, the intensity of the irradiated laser, etc., but a person skilled in the art can set the appropriate conditions without excessive testing. For example, a non-irradiated area may be provided next to the laser-irradiated area with the same width as the laser drawing line width. In this way, the second substrate can be separated even when only a portion of the adhesive layer is irradiated with the laser, thereby shortening the laser irradiation time per laminate and, as a result, the total time required for peeling can be shortened. EXAMPLES

[0155] (1) Mixer: Thinky Corporation, Planetary Planetary Mixer ARE-500 (2) Viscometer: Rotational viscometer TVE-22H manufactured by Toki Sangyo Co., Ltd. (3) Ultrasonic device: ASU CLEANER (AS ONE, ASU-6) (4) Measurement of transmittance: Shimadzu Corporation UV2550 UV-Visible Spectrophotometer (5) Vacuum bonding device: SUSS MicroTec, manual bonder (6) 308 nm laser irradiation device: SUSS MicroTec Co., Ltd., 308 nm laser irradiation device (7) 355 nm laser irradiation device: Lotus-TII LT-2137 (8) 532 nm laser irradiation device: Lotus-TII LT-2137 (9) Infrared radiation thermometer: Testo Corporation, Infrared radiation thermometer 835-H1

[0156] [1] Preparation of the composition [Preparation Example 1] In a 600 mL stirring vessel for the stirrer, 80 g of MQ resin (manufactured by Wacker Chem.) containing polysiloxane and vinyl groups as polyorganosiloxane (a1), 2.52 g of SiH group-containing linear polydimethylsiloxane (manufactured by Wacker Chem.) with a viscosity of 100 mPa·s as polyorganosiloxane (a2), 5.89 g of SiH group-containing linear polydimethylsiloxane (manufactured by Wacker Chem.) with a viscosity of 70 mPa·s as polyorganosiloxane (a2), and 0.22 g of 1-ethynyl-1-cyclohexanol (manufactured by Wacker Chem.) as polymerization inhibitor (A3) were placed and stirred with the stirrer for 5 minutes.

[0157] To the resulting mixture, 0.147 g of platinum catalyst (manufactured by Wacker Chem.) as the platinum group metal catalyst (A2) and 5.81 g of vinyl group-containing linear polydimethylsiloxane (manufactured by Wacker Chem.) with a viscosity of 1000 mPa·s as the polyorganosiloxane (a1) were stirred for 5 minutes with a stirrer, and 3.96 g of the resulting mixture was added and stirred for 5 minutes with a stirrer.

[0158] Finally, the resulting mixture was filtered through a 300 mesh nylon filter to obtain a precursor composition (P).

[0159] [Example 1-1] In a 200 mL stirring vessel for the stirrer, 19.7 g of the precursor composition (P), 0.04 g of 1,1-diphenyl-2-propyne-1-ol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a polymerization inhibitor (A3), and 1,000,000 mm2 of component (B) containing a component containing polydimethylsiloxane were added. 2 8.54 g of polyorganosiloxane (manufactured by Wacker Chem, product name AK1000000) was added and stirred with a stirrer for 5 minutes.

[0160] To the obtained mixture, 0.40 g of thioindigo (manufactured by Tokyo Chemical Industry Co., Ltd.) as a light absorbing organic compound (X), 4.92 g of silica particles X-52-854 (manufactured by Shin-Etsu Chemical Co., Ltd.), and 11.82 g of mesitylene (manufactured by Tokyo Chemical Industry Co., Ltd.) were added to a 50 mL screw tube, and the mixture was ultrasonically treated for 5 minutes using an ultrasonic device, and then added to the mixture, which was then stirred for 5 minutes using a stirrer.

[0161] Finally, the mixture was filtered through a 5.0 μm PTFE filter to obtain a composition for light irradiation peeling.

[0162] [Example 1-2] In a 200 mL stirring vessel for the stirrer, 19.7 g of the precursor composition (P), 0.04 g of 1,1-diphenyl-2-propyne-1-ol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a polymerization inhibitor (A3), and 1,000,000 mm2 of component (B) containing a component containing polydimethylsiloxane were added. 2 8.54 g of polyorganosiloxane (manufactured by Wacker Chem, product name AK1000000) was added and stirred with a stirrer for 5 minutes.

[0163] To the obtained mixture, 0.40 g of Oralis Brilliant Pink R (manufactured by Tokyo Chemical Industry Co., Ltd.) as a light absorbing organic compound (X), 4.92 g of silica particles X-52-854 (manufactured by Shin-Etsu Chemical Co., Ltd.), and 11.82 g of mesitylene (manufactured by Tokyo Chemical Industry Co., Ltd.) were added to a 50 mL screw tube, and the mixture was ultrasonically treated for 5 minutes using an ultrasonic device, and then added to the mixture, which was then stirred for 5 minutes using a stirrer.

[0164] Finally, the mixture was filtered through a 5.0 μm PTFE filter to obtain a composition for light irradiation peeling.

[0165] [Examples 1-3] In a 200 mL stirring vessel for the stirrer, 19.7 g of the precursor composition (P), 0.04 g of 1,1-diphenyl-2-propyne-1-ol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a polymerization inhibitor (A3), and 1,000,000 mm2 of component (B) containing a component containing polydimethylsiloxane were added. 2 8.54 g of polyorganosiloxane (manufactured by Wacker Chem, product name AK1000000) was added and stirred with a stirrer for 5 minutes.

[0166] To the obtained mixture, 0.40 g of thioindigo (manufactured by Tokyo Chemical Industry Co., Ltd.) and 11.82 g of mesitylene (manufactured by Tokyo Chemical Industry Co., Ltd.) were added as light absorbing organic compound (X) in a 50 mL screw tube, and a mixture obtained by ultrasonicating this for 5 minutes using an ultrasonic device was added, and the mixture was stirred for 5 minutes using a stirrer.

[0167] Finally, the resulting mixture was filtered through a 5.0 μm PTFE filter to obtain a photoirradiation peeling composition.

[0168] [Comparative Example 1-1] In a 200 mL stirring vessel for the stirrer, 19.7 g of the precursor composition (P), 0.04 g of 1,1-diphenyl-2-propyne-1-ol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a polymerization inhibitor (A3), and 1,000,000 mm2 of component (B) containing a component containing polydimethylsiloxane were added. 2 8.54 g of polyorganosiloxane (manufactured by Wacker Chem, product name AK1000000) was added and stirred with a stirrer for 5 minutes.

[0169] The obtained mixture was added to a 50 mL screw tube containing 4.92 g of silica particles X-52-854 (manufactured by Shin-Etsu Chemical Co., Ltd.) and 11.82 g of mesitylene (manufactured by Tokyo Chemical Industry Co., Ltd.), which had been subjected to ultrasonic treatment for 5 minutes using an ultrasonic device, and the mixture was then stirred for 5 minutes using a stirrer.

[0170] Finally, the resulting mixture was filtered through a 5.0 μm PTFE filter to obtain a composition.

[0171] [Comparative Example 1-2] Instead of thioindigo, New Coccine, a low molecular weight compound known to have light absorption ability, was used, but the same method as in Example 1-1 was used to prepare the composition, but precipitation was observed in the composition, and it was not possible to obtain a composition that was homogeneous enough to be used to form a thin film.In addition, since it was clear that filtration failure would occur, filtration was not performed.

[0172] [ka]

[0173] [Reference example 1-1] In a 200 mL stirring vessel for the stirrer, 19.7 g of the precursor composition (P), 0.04 g of 1,1-diphenyl-2-propyne-1-ol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a polymerization inhibitor (A3), and 1,000,000 mm2 of component (B) containing a component containing polydimethylsiloxane were added. 2 8.54 g of polyorganosiloxane (manufactured by Wacker Chem, product name AK1000000) having a molecular weight of 1 / s was added, and the mixture was stirred for 5 minutes with a stirrer. Finally, the mixture was filtered through a 5.0 μm PTFE filter to obtain a composition.

[0174] [2] Thin film formation and transmittance measurement [Example 2-1] The composition obtained in Example 1-1 was applied onto a quartz substrate using a spin coater, and heated on a hot plate at 120° C. for 1.5 minutes and then at 200° C. for 10 minutes to form a thin film with a thickness of 30 μm.

[0175] [Examples 2-2 to 2-3, Comparative Example 2-1 and Reference Example 2-1] Thin films were formed in the same manner as in Example 2-1, except that the compositions obtained in Examples 1-2 to 1-3, Comparative Example 1-1, and Reference Example 1-1 were used instead of the composition obtained in Example 1-1.

[0176] To determine whether the obtained thin film can be used as a layer for laser peeling, the transmittance of light with wavelengths of 308 nm and 532 nm was measured. The results are shown in Table 1.

[0177] Compared to the thin film obtained in Reference Example 2-1, the thin films obtained in Examples 2-1 to 2-3 contained thioindigo, and therefore had reduced transmittance for 308 nm and 532 nm lasers, suggesting that the thin films are applicable to laser peeling.

[0178] On the other hand, the thin film obtained in Comparative Example 2-1 also exhibited a decrease in transmittance, even though it did not contain thioindigo. This is due to light scattering caused by the silica particles contained in the thin film.

[0179] [Table 1]

[0180] [3] Confirmation of optimal irradiation dose and heat generation during laser (308 nm) peeling [Example 3-1] The composition obtained in Example 1-1 was applied to a 100 mm silicon wafer (thickness 500 μm) as the device side wafer by a spin coater, and heated on a hot plate at 120° C. for 1.5 minutes to form a thin film. The wafer (support) on the carrier side was a 100 mm glass wafer (EAGLE-XG, Corning, thickness 500 μm) and bonded in a vacuum bonding apparatus so as to sandwich the thin film formed, and the wafer was heated on a hot plate at 200° C. for 10 minutes with the device side wafer facing down to harden the thin film formed, thereby obtaining a laminate. The bonding was performed at a temperature of 25° C., a vacuum degree of 1,000 Pa, and a load of 30 N.

[0181] [Example 3-2] A laminate was obtained in the same manner as in Example 3-1, except that the composition obtained in Example 1-2 was used instead of the composition obtained in Example 1-1.

[0182] The obtained laminate was irradiated with a laser having a wavelength of 308 nm from the glass wafer side using a laser irradiation device. At this time, the output was changed to 100 to 500 mJ / cm. 2 The minimum irradiation dose at which peeling occurred was confirmed.

[0183] As a result, in all laminates, the maximum irradiation energy was 300 mJ / cm 2 This value was determined as the optimal irradiation dose, and peeling tests were then carried out using a laser with a wavelength of 308 nm.

[0184] In order to confirm whether heat was generated during the laser irradiation, the temperature of the laminate was measured before and after the laser irradiation using an infrared radiation thermometer.

[0185] As a result, the temperature of each laminate was about 24° C. before the laser irradiation and about 21° C. after the laser irradiation, and it was determined that the film did not substantially generate heat due to the laser irradiation.

[0186] [4] Confirmation of peelability using a 308 nm laser (confirmation of peelability by irradiating the entire surface) [Examples 4-1 to 4-2] A laser with a wavelength of 308 nm was irradiated from the glass wafer side of the laminate obtained by the same method as in Examples 3-1 and 3-2 using a laser irradiation device to confirm whether the glass wafer could be peeled off. At this time, the laser was irradiated so as not to overlap front, back, left and right. The laser output was 300 mJ / cm in all Examples. 2 It was decided.

[0187] As a result, it was confirmed that in both the laminates of Examples 4-1 and 4-2, the glass wafer (carrier side) could be easily peeled off manually with almost no force.

[0188] [5] Confirmation of optimal irradiation dose and heat generation during laser (532 nm) peeling [Examples 5-1 to 5-2] Laminates were obtained in the same manner as in Examples 3-1 and 3-2, respectively.

[0189] [Example 5-3] A laminate was obtained in the same manner as in Example 5-1, except that the composition obtained in Example 1-3 was used instead of the composition obtained in Example 1-1.

[0190] [Comparative Example 5-1] A laminate was obtained in the same manner as in Example 5-1, except that the composition obtained in Comparative Example 1-1 was used instead of the composition obtained in Example 1-1.

[0191] The obtained laminate was irradiated with a laser having a wavelength of 532 nm from the glass wafer side using a laser irradiation device. At this time, the output was changed to 20 to 160 mJ / cm. 2 The minimum irradiation dose at which peeling occurred was confirmed.

[0192] As a result, the laminate of Example 5-1 had an energy of 300 mJ / cm 2 400 mJ / cm for the laminate of Example 5-2 2 500 mJ / cm for the laminate of Example 5-3 2 Peeling was confirmed in the laminate of Comparative Example 5-1, whereas no peeling was confirmed in the laminate of Comparative Example 5-1. Regarding the laminates of the Examples, the respective values ​​obtained were regarded as the optimal irradiation dose, and peeling tests were carried out using a laser with a wavelength of 532 nm as follows.

[0193] Furthermore, in order to confirm whether heat was generated during laser irradiation, the temperatures of the laminates of Examples 5-1 and 5-2 were measured before and after laser irradiation using an infrared radiation thermometer.

[0194] As a result, the temperature of the laminate was about 21° C. before the laser irradiation and about 25° C. after the laser irradiation, and it was determined that the film did not substantially generate heat due to the laser irradiation.

[0195] [6] Confirmation of peelability using a 532 nm laser (confirmation of peelability by irradiating the entire surface) [Examples 6-1 to 6-2] A laser with a wavelength of 532 nm was irradiated from the glass wafer side of the laminate obtained by the same method as in Examples 5-1 and 5-2 using a laser irradiation device to confirm whether the glass wafer could be peeled off. At this time, the laser was irradiated so as not to overlap front, back, left and right. The laser output in Example 6-1 was 300 J / cm. 2 , 400 J / cm in Example 6-2 2 It was decided.

[0196] As a result, it was confirmed that in all the laminates, the glass wafer (carrier side) could be easily peeled off manually with almost no force.

[0197] [7] Confirmation of optimal irradiation dose and heat generation during laser (355 nm) peeling [Examples 7-1 to 7-2] Laminates were obtained in the same manner as in Examples 3-1 and 3-2, respectively.

[0198] [Comparative Example 7-1] A laminate was obtained in the same manner as in Example 7-1, except that the composition obtained in Comparative Example 1-1 was used instead of the composition obtained in Example 1-1.

[0199] The obtained laminate was irradiated with a laser having a wavelength of 355 nm from the glass wafer side using a laser irradiation device. At this time, the output was changed to 20 to 80 mJ / cm. 2 The minimum irradiation dose at which peeling occurred was confirmed.

[0200] As a result, the laminates of Examples 7-1 and 7-2 had a maximum energy of 160 mJ / cm 2 Peeling was confirmed in the laminate of Comparative Example 7-1, and no peeling was confirmed in the laminate of Comparative Example 7-1. Regarding the laminates of the Examples, the respective values ​​obtained were taken as the optimum irradiation amount, and peeling tests were carried out using a laser with a wavelength of 355 nm as follows.

[0201] Furthermore, in order to confirm whether heat was generated during laser irradiation, the temperatures of the laminates of Examples 7-1 and 7-2 were measured before and after laser irradiation using an infrared radiation thermometer.

[0202] As a result, the temperature of the laminate was about 22° C. before the laser irradiation and about 23° C. after the laser irradiation, and it was determined that the film did not substantially generate heat due to the laser irradiation.

[0203] [8] Confirmation of peelability using a 355 nm laser (confirmation of peelability by irradiating the entire surface) [Examples 8-1 to 8-2] A laser with a wavelength of 355 nm was irradiated from the glass wafer side of the laminate obtained in the same manner as in Examples 7-1 and 7-2 using a laser irradiation device to confirm whether the glass wafer could be peeled off. At this time, the laser was irradiated so as not to overlap front, back, left and right. The laser output was 160 mJ / cm for both Examples 8-1 and 8-2. 2 It was decided.

[0204] As a result, it was confirmed that in all the laminates, the glass wafer (carrier side) could be easily peeled off manually with almost no force.

Claims

1. A light-irradiation peelable adhesive composition that can be peeled off by light irradiation, The adhesive composition includes an adhesive component (S) including a component (A) that cures by a hydrosilylation reaction, and a light-absorbing organic compound (X), the light absorbing organic compound (X) contains, in the molecule, one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more groups selected from a carbonyl group and a thiocarbonyl group; the carbon atom of the carbonyl group or the thiocarbonyl group is a ring-constituting atom of a ring that contains a heteroatom as a ring-constituting atom; The light-irradiation peelable adhesive composition is characterized in that the light-absorbing organic compound (X) is represented by formula (T1-1) or (T2-1). 【Chemistry 1】 (X 1 ~X 4 are carbon atoms constituting an aromatic ring, and are each independently bonded to a hydrogen atom, a halogen atom or a monovalent organic group other than the carbon atom constituting the aromatic ring; X 5 each independently represents a heteroatom; and X 6 is an oxygen atom or a sulfur atom.

2. A light-irradiation peelable adhesive composition that can be peeled off by light irradiation, The adhesive composition includes an adhesive component (S) including a component (A) that cures by a hydrosilylation reaction, and a light-absorbing organic compound (X), the light absorbing organic compound (X) contains, in its molecule, one or more aromatic rings, one or more rings containing a heteroatom as a ring-constituting atom, and one or more carbonyl groups or thiocarbonyl groups; the carbon atom of the carbonyl group or the thiocarbonyl group is a ring-constituting atom of a ring that contains a heteroatom as a ring-constituting atom; The light-irradiation peelable adhesive composition is characterized in that the light-absorbing organic compound (X) is represented by formula (T1-1) or (T2-1). 【Chemistry 2】 (X 1 ~X 4 are carbon atoms constituting an aromatic ring, and are each independently bonded to a hydrogen atom, a halogen atom or a monovalent organic group other than the carbon atom constituting the aromatic ring; X 5 each independently represents a heteroatom; and X 6 is an oxygen atom or a sulfur atom.

3. 3. The adhesive composition for peeling off upon light irradiation according to claim 1 or 2, wherein the light absorbing organic compound (X) contains, in its molecule, two or more aromatic rings, two or more rings containing the heteroatom as a ring-constituting atom, and two or more carbonyl groups or thiocarbonyl groups.

4. 3. The light-irradiation peelable adhesive composition according to claim 1, wherein the light-absorbing organic compound (X) is a thioindigo derivative or an isothioindigo derivative.

5. 5. The light irradiation peelable adhesive composition according to claim 4, wherein the thioindigo derivative or isothioindigo derivative is represented by formula (T1-2) or (T2-2): 【Chemistry 3】 (In the formula, each R A are atoms or groups substituted on the benzene ring, each independently representing a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or an aryl group, and a to d are each independently an integer of 0 to 4.

6. 6. The light-irradiation peelable adhesive composition according to claim 5, wherein the thioindigo derivative or isothioindigo derivative is represented by formula (T1-3) or (T2-3): 【Chemistry 4】 (In the formula, each R B And each R C each independently represents a hydrogen atom, a halogen atom, or an alkyl group.

7. The adhesive composition for peeling off upon light irradiation according to any one of claims 1 to 6, further comprising a component (B) containing at least one selected from the group consisting of a component containing an epoxy-modified polyorganosiloxane, a component containing a methyl group-containing polyorganosiloxane, and a component containing a phenyl group-containing polyorganosiloxane.

8. The component (A) that cures by a hydrosilylation reaction is SiO 2 Siloxane units (Q units) represented by the formula: R 1 R 2 R 3 SiO 1/2 Siloxane units (M units) represented by the formula: R 4 R 5 SiO 2/2 Siloxane units (D units) represented by the formula: 6 SiO 3/2 Polysiloxane (A1) containing one or more units selected from the group consisting of siloxane units (T units) represented by the following formula: 1 ~R 6 are a group or atom bonded to a silicon atom, and each independently represent an alkyl group, an alkenyl group, or a hydrogen atom; and a platinum group metal catalyst (A2), The polysiloxane (A1) is SiO 2 Siloxane units (Q′ units) represented by the formula: 1 'R 2 'R 3 'SiO 1/2 Siloxane units (M′ units) represented by the formula: 4 'R 5 'SiO 2/2 Siloxane units (D′ units) represented by the formula: 6 'SiO 3/2 Polyorganosiloxane (a1) (the above R 1 '~R 6 Each of R ′ is a group bonded to a silicon atom, and each independently represents an alkyl group or an alkenyl group. 1 '~R 6 At least one of the groups represented by the formula (I) is an alkenyl group. 2 Siloxane units (Q″ units) represented by the formula: 1 "R 2 "R 3 "SiO 1/2 Siloxane units (M″ units) represented by the formula: 4 "R 5 "SiO 2/2 Siloxane units (D″ units) represented by the formula: 6 "SiO 3/2 and at least one unit selected from the group consisting of the M″ unit, the D″ unit and the T″ unit. 1 "~R 6 " are groups or atoms bonded to a silicon atom, and each independently represents an alkyl group or a hydrogen atom. 1 "~R 6 8. The light irradiation peelable adhesive composition according to claim 1, wherein at least one of said groups is a hydrogen atom.

9. A laminate including a first base made of a semiconductor forming substrate, a second base made of a support substrate that transmits laser light, and an adhesive layer, A laminate, wherein the adhesive layer is a cured film obtained from the photoirradiation peelable adhesive composition according to any one of claims 1 to 8.

10. A first step of coating a surface of a first substrate or a second substrate with the light irradiation peelable adhesive composition according to any one of claims 1 to 8 to form an adhesive coating layer; a second step of bonding the first substrate and the second substrate via the adhesive coating layer, applying a load in the thickness direction of the first substrate and the second substrate while performing at least one of a heat treatment and a decompression treatment, thereby adhering the first substrate, the adhesive coating layer, and the second substrate to each other, and then performing a post-heat treatment.

11. A peeling method, comprising irradiating a laser from the second substrate side of the laminate obtained by the method for producing a laminate according to claim 10, thereby peeling off the second substrate.

12. The peeling method according to claim 11, wherein the laser has a wavelength of 190 nm to 600 nm.

Citation Information

Patent Citations

  • Laser recording material and image forming method

    JP1986295076A

  • Laminate including substrate to be ground, method of manufacturing the same, method of manufacturing ultrathin substrate using the laminate, and apparatus therefor

    JP2004064040A

  • Laminated body and method for separating laminated body

    JP2012106486A

  • Substrate processing method, semiconductor device and manufacturing method thereof

    JP2017050322A

  • Method for fixing infrared-reflective dark protection sheet

    JP2019128387A